ANALISIS PREFERENSI MEDIA INFORMASI PENCEGAHAN MALARIA PADA IBU HAMIL DI WILAYAH PUSKESMAS SENTANI - Susi Lestari; Arum Surya Utami; Tiyan Febriyani Lestari; Fetty Satu Ryan Utami (Jurnal Ners, 2026)
Malaria is a major health problem in Papua Province with a high prevalence and impacts pregnant women, infants, and community productivity. Behavioral factors such as the use of mosquito nets, home environmental conditions, and community knowledge influence the risk of malaria. To support control efforts, this study was conducted to understand the preferences of malaria prevention information media among pregnant women at the Sentani Community Health Center. This study used a non-experimental survey design with a cross-sectional approach that measured variables once without follow-up. The dependent variable was information media preference, while the independent variables included age, education, occupation, knowledge, access to technology, and frequency of information media use. Data were obtained through questionnaires to pregnant women as respondents. The results showed that the majority of pregnant women were aged 20–35 years, had moderate education, were unemployed, had internet access, and had good knowledge about malaria. The most preferred information media was direct counseling (44.4%), followed by digital media (33.3%) and print media (22.2%). There was a significant relationship between age and information media preference (p=0.043), while education, occupation, access to technology, number of pregnancies, and knowledge did not show a significant relationship. In conclusion, direct counseling remains the preferred information medium because it is considered easier to understand and interactive.